A theory of the elastic-viscoplastic Cosserat continuum - Sansour, C. (Archives of Mechanics, 1998)
Based on the multiplicative decomposition of the stretch tensor and the additive decomposition of the second Cosserat deformation tensor into elastic and inelastic parts, a theory of the elastic-viscoplastic Cosserat continuum is formulated. It is stressed that the rotation field is to be treated as a kinematical variable which can not be decomposed into elastic and inelastic parts. A thorough discussion of the configuration space by relying on basic concepts of Lie groups is provided and the field equations are derived from a variational statement. The flow rules are specified by means of the postulate of maximum dissipation paralleling some developments of the classical theory.